A Longitudinal Electromyography Study of Complex Movements in Poststroke Therapy. 2: Changes in Coordinated Muscle Activation - Hesam-Shariati, Negin; Trinh, Terry; Thompson-Butel, Angelica G.; Shiner, Christine T.; McNulty, Penelope A. (Frontiers in Neurology, 2017)
Fine motor control is achieved through the co-ordinated activation of groups of muscles, or "muscle synergies". Muscle synergies change after stroke as a consequence of the motor deficit. We investigated the pattern and longitudinal changes in upper-limb muscle synergies during therapy in a largely unconstrained movement in patients with a broad spectrum of post-stroke residual voluntary motor capacity. Electromyography (EMG) was recorded using wireless telemetry from 6 muscles acting on the more-affected upper body in 24 stroke patients at early- and late-therapy during formal Wii-based Movement Therapy sessions, and in a subset of 13 patients at 6-month follow-up. Patients were classified with low, moderate or high motor-function. The Wii-baseball swing was analysed using a non-negative matrix factorisation (NMF) algorithm to extract muscle synergies from EMG recordings based on the temporal activation of each synergy and the contribution of each muscle to a synergy. Motor-function was clinically assessed immediately pre- and post-therapy and at 6-month follow-up using the Wolf Motor Function Test, upper-limb motor Fugl-Meyer Assessment and Motor Activity Log Quality of Movement scale. Clinical assessments and game performance demonstrated improved motor-function for all patients at post-therapy (p<0.01) and these improvements were sustained at 6-month follow-up (p>0.05). NMF analysis revealed fewer muscle synergies (mean±SE) for patients with low motor-function (3.38±0.2) than those with high motor-function (4.00±0.3) at early-therapy (p=0.036) with an association trend between the number of synergies and the level of motor-function. By late-therapy there was no significant change between groups, although there was a pattern of increase for those with low motor-function over time. The variability accounted for (VAF) demonstrated differences with motor-function level but not time (p<0.05). Cluster analysis of the pooled synergies highlighted the therapy-induced change in muscle activation. Muscle synergies could be identified for all patients during therapy activities. These results show less complexity and more co-activation in the muscle activation for patients with low motor-function as a higher number of muscle synergies reflects greater movement complexity and task-related phasic muscle activation. The increased number of synergies and changes within synergies by late-therapy suggests improved motor control and movement quality with more distinct phases of movement.